Variant of Poland's Syndrome: Hypoplasia of The Unilateral Breast and Pectoral Muscle - Yılmaz, Sevda; Tellioğlu, Ali Teoman (Fırat University, 2006)
Poland's syndrome is an uncommon congenital and unilateral anomaly of the breast and thoracic cage. It may be associated with other anomalies of the ipsilateral upper extremity. We herein report a rare case of a patient with hypoplasia of the left breast and absent of the left anterior axillary fold being the sole clinical manifestation of this syndrome.©2006, Fırat Üniversitesi, Tıp Fakültesi

Poland sendromu, göğüs kafesi ve memenin nadir görülen tek taraflı ve doğumsal bir anomalisidir. Aynı taraf üst ekstremitenin diğer anomalilerine eşlik edebilir. Nadir görülen ve tek klinik bulgusu sol memede hipoplazi ile anterior aksiller fold yokluğu olan ve nadir görülen bir olguyu sunuyoruz ©2006, Fırat Üniversitesi, Tıp Fakültesi
Poland Sendromu Varyantı: Tek Taraflı Meme ve Pektoral Kas Hipoplazisi